A invenção de Brasília: o" risco" de Lúcio Costa - Barki, José (Risco - Journal of Architecture and Urbanism, 2005)
The commemorative exhibition marking Lucio Costa's birth centennial that took place at the "Paço Imperial", Rio de Janeiro, from March to April 2002, showed a surprising collection of study drafts for the Capital-City of Brasilia (1956/1957) design competition. This paper attempts to document and critically analyze these sketches from a renewed methodological perspective of research, which scrutinizes its 'design logic'.